Investigating the metabolic changes that accompany skeletal muscle hypertrophy - Rimmer, Linnea (Kansas State University, 2023)
The meat industry must increase production output with fewer agricultural inputs to sustain the growing global population. Innovative strategies to improve feed efficiency in swine can reduce production expenses and feed requirements. Skeletal muscle is responsible for up to 90% of all glucose use in meat producing animals, and therefore has become a target to improve nutrient utilization efficiency. For example, an increase in muscle oxidative capacity is associated with lower feed efficiency in pigs. To define the metabolic changes in skeletal muscle that accompany maturation, samples were collected from the longissimus dorsi (LD, glycolytic muscle), latissimus dorsi (LAT, mixed muscle), and masseter (MS, oxidative muscle) at 20, 53, 87, 120, and 180 days of age from DNA 600 x 241 (DNA Genetics) castrated male pigs that weighed an average of 5.7, 20.8, 42.2, 83.4, and 130.5 kg, respectively. Ages correspond to the end of each phase diet typical of those fed in commercial production, which are formulated to meet nutrient requirements to support each period of growth. Muscles were assessed to determine the abundance of several metabolic enzymes through Western blotting. Additionally, mitochondria were isolated and incubated with [¹³C₃]-pyruvate in an in vitro tracing model to analyze isotopomer enrichment patterns of tricarboxylic acid cycle (TCA) intermediates to investigate how mitochondria metabolize pyruvate. Glucose-6-phosphate dehydrogenase decreased at 87, 120, and 180 d in MS compared to LAT and LD (P < 0.01), which suggests glycolytic muscles increase intermediate allocation to the pentose phosphate pathway at this time whereas oxidative muscles do not. Moreover, pyruvate carboxylase (PC) increased at 53 d compared to 20, 87, 120, and 180 d (P < 0.01), while pyruvate dehydrogenase increased at 120 d compared to 53 d (P < 0.05) indicating there was a shift in pyruvate entry into the TCA cycle. Oxaloacetate M3 mole percent excess and citrate synthase increased at 120 d (P < 0.01), while citrate M3 mole percent excess decreased at 120 d (P < 0.01). These data suggest pyruvate-derived citrate exits the TCA cycle at 120 d by an unidentified cataplerotic reaction. Additionally, alpha-ketoglutarate M3 mole percent excess increased at 180 d in LD and LAT compared to MS (P < 0.01), and abundance of glutamate dehydrogenase increased at 180 d (P < 0.05), which indicates a portion of pyruvate-derived carbons could be exiting the TCA cycle at 180 d through glutamate dehydrogenase. These findings have established a metabolic fingerprint associated with muscle hypertrophy and provides the framework to uncover the regulatory mechanism that modulates nutrient allocation to major metabolic pathways in growing muscle. Elucidating this mechanism will aid in providing innovative strategies to improve feed efficiency in the swine industry.
Keywords: Skeletal muscle metabolism; Feed efficiency; Nutrient utilization; Swine